Congenital combined deficiency of coagulation factors: a study of seven patients. Issue 1 (January 2015) - Naderi, Majid; Tabibian, Shadi; Hosseini, Maryam Sadat; Alizadeh, Shaban; Hosseini, Soudabeh; Shamsizadeh, Morteza; Dorgalaleh, Akbar
Abstract : Combined deficiency of coagulation factors is considered as an extremely rare bleeding disorder (RBD) inherited in an autosomal recessive pattern. This disorder is more likely to occur in regions with a high rate of consanguineous marriages or in restricted communities. Sistan and Baluchistan, a province in southeast of Iran with a high rate of consanguinity, is a clear model of such regions with a very high prevalence of recessively inherited disorders. The aim of this study was to report the frequency of combined factor deficiency in this province. This descriptive study was conducted on 358 patients with RBD. Demographic information and medical history of each patient were recorded, and the patients were examined by a physician. Routine screening tests were carried out for all patients, and further coagulation tests including coagulation factor activity and antigen assays were subsequently performed for all suspected patients. Among 358 patients, four were found to be affected with combined factor (F)V and FVIII deficiency (F5F8D). In addition, one patient with combined deficiency of FVII-FXIII, one with combined FVII-FX and one with combined FVIII-FIX deficiency were identified. In Sistan and Baluchistan Province, coinheritance of recessively inherited disorders like combined coagulation factor deficiencies was surprisingly higher than expected.